PENGARUH PERTUMBUHAN EKONOMI TERHADAP DISPARITAS PENDAPATAN DI INDONESIA - Sayifullah Sayifullah (Jurnal Ekonomi-Qu, 2021)
The purpose of this research is to prove the influence and relationship of economic growth on income disparity in Indonesia. Panel data analysis is used to see the effect and relationship of economic growth on income disparity. The results showed that economic growth has positive relation but did not significantly affect the disparity on income distribution. When viewed in the development of economic growth, the existence of economic growth in each province shows the development of economic growth rates that are much different, although in each of these provinces most of them show an increase every year. So that the influence of economic growth is not yet significant due to the value of economic growth rates that are far different, where when economic growth increases but income distribution cannot be felt by all groups.